2011
DOI: 10.1103/physrevd.83.063502
|View full text |Cite
|
Sign up to set email alerts
|

Generalizing a unified model of dark matter, dark energy, and inflation with a noncanonical kinetic term

Abstract: We study a unification model for dark energy, dark matter, and inflation with a single scalar field with non canonical kinetic term. In this model the kinetic term of the Lagrangian accounts for the dark matter and dark energy, and at early epochs a quadratic potential accounts for slow roll inflation. The present work is an extension to the work by Bose and Majumdar [Phys. Rev. D 79, 103517 (2009).] with a more general kinetic term that was proposed by Chimento in Phys. Rev. D 69, 123517 (2004). We demonstra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…Unnikrishnan et al [57] have showed that for such models, the slow-roll conditions can be more easily satisfied compared to the canonical case. The non-canonical scalar field models are also found to be able to generate inflation in the early epoch [45,[47][48][49][50][51][52][53][54][55][56][57][58][59]. These attractive features of a noncanonical scalar field motivated us to study the features of this model in the context of dark energy.…”
Section: Field Equations and Their Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unnikrishnan et al [57] have showed that for such models, the slow-roll conditions can be more easily satisfied compared to the canonical case. The non-canonical scalar field models are also found to be able to generate inflation in the early epoch [45,[47][48][49][50][51][52][53][54][55][56][57][58][59]. These attractive features of a noncanonical scalar field motivated us to study the features of this model in the context of dark energy.…”
Section: Field Equations and Their Solutionsmentioning
confidence: 99%
“…In the non-canonical scalar field models, the kinetic part of the scalar field is modified and it has been found that an accelerated expansion can be achieved through these modifications. Originally, Armendariz-Picon et al [45,46] proposed this scenario to explain inflation at high energies where the non-canonical scalar field efficiently plays the role of inflaton (for review on this topic, see [45,[47][48][49][50][51][52][53][54][55][56][57][58][59]). Later, Chiba et al [13] introduced this scenario for dark energy models.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the former choices for Ω(φ) and ω(φ) change the kinetic term of (6) into a suitable canonical form. At the end of inflation, the scalar field with the plateau-like potential (11) has an oscillatory phase of evolution around φ = 0 and at the late time this potential is dominated byV (φ) ≈ V * α which can be interpreted as remnant dark energy [20][21][22][23][24][25][26][27][28][29].…”
Section: Building a Non-minimal Coupling Model In The Einstein Framementioning
confidence: 99%
“…(11)) which satisfies the constraints of recent CMB data and reheating analysis. This model has another interesting properties such as a remnant energy density appropriate to describe the recent accelerated expansion of the universe which has recently received attention [20][21][22][23][24][25][26][27][28][29]. We start with a quadratic potential coupled non-minimally to the gravity in the Jordan frame and then move to the Einstein frame by employing a special conformal transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Within the models investigated in order to unify DE and DM are the GCG [38,[54][55][56][57][58][59][60] and those known as purely kinetic models [39,61]. The unification of DE, DM, and inflation has been addressed in [62,63].…”
Section: Introductionmentioning
confidence: 99%